Influence of Link Structure on Search Engine Result Pages of Online Nursery Shops - Pongracz, Norman (My University, 2012)
The primary objective of this thesis is to assess how the backlink portfolio structure and off site Search Engine Optimisation (SEO) elements influence ranking of UK based online nursery shops. The growth of the internet use demanded significant effort from companies to optimize and increase their online presence in order to cope with the increasing online competition. The new e-Commerce technology - called Search Engine Optimisation - has been developed that helped increase website visibility of companies. The SEO process involves on site elements (i.e. changing the parameters of the company's website such as keywords, title tags and meta descriptions) and off site elements (link building and social media marketing activity). Link Building is based on several steps of marketing planning including keyword research and competitor analysis. The underlying goal of keyword research is to understand the targeted market through identifying relevant keyword queries that are used by targeted costumer group. In the analysis, three types (geographic, field and company’s strategy related) and seven sources of keywords has been identified and used as a base of analysis. Following the determination of the most popular keywords, allinanchor and allintitle search has been conducted and the first ten results of the searches have been collected to identify the companies with the most significant web presence among the nursery shops. Finally, Link Profiling has been performed where the essential goal was to understand to what extent other companies' link structure is different that the base company's backlinks. Significant difference has been found that distinguished the top three companies ranking in the allinanchor and allintitle search. The top three companies, „Mothercare”, „Mamas and Papas” and „Kiddicare” maintained significantly better metrics regarding domain and page authority on the main landing pages, the average number of outbound links for link portfolio metric and in number of backlinks. These companies also ranked among the highest in page authority distribution and followed external linking.